Representações do trabalho escravo a partir da mídia : olhares de trabalhadores rurais maranhenses - Moura, Flávia de Almeida (2015)
This study analyzes the measures of a group of maranhense field workers which appropriates of the television journalistic text to have their own representation of slave labor. We used as main methodological strategy the assistance of television journalistic materials within the individuals investigated to trigger the dialogue on contemporary representations of slave labor from the media. In this sense, the TV news is part of the universe of our documentary corpus, which was cut in seven articles published in open channels of Brazilian television between the years 2009 and 2013, period related even with the experiences of the workers interviewed with slave labor even as our contact and follow up with the empirical object. We are interested in the processes of identification and ownership of the workers interviewed by the media text displayed during the field work, conducted in the city of Açailândia, Maranhão, one of the major in incidence of contemporary slavery in Brazil. In this path, we faced different views of these subjects about the representations of slave labor displayed by the media. And it is on these looks, parts of this social group and the media, that this thesis focuses.